Relationship between level of red blood cell indices and risk of gestational diabetes mellitus: a case-control study - Mahta Abbasi Fashami; Sepideh Hajian; Maryam Afrakhteh; Mehdi Khabaz Khoob (Mashhad University of Medical Sciences, 2019)
Introduction: Gestational diabetes mellitus (GDM) is the most common metabolic disorder in pregnancy. According to maternal-fetal complications of GDM, recognizing the related factors is crucial. There is evidence of association between some red blood cell indices such as hemoglobin and gestational diabetes. This study was performed with aimed to determine the relationship between level of red blood cells indices and risk of GDM occurrence. Methods: This case-control study was performed on 190 pregnant women with and without GDM referred to the prenatal care clinic of Tajrish Shohada hospital from October 2017 to March 2018. GDM screening tests was done by oral glucose tolerance test)OGTT) with 75-gr glucose and complete blood cell count measurement in gestational age of 24-28. Data was analyzed using SPSS software (version 16) and independent t-test, Mann-Whitney, Correlation, and logistic regression. PResults: Except than mean cellular weight (p= 0.06), other red blood cell indices (including red blood cell, hemoglobin, hematocrit, mean corpuscular volume and mean corposcular hemoglobin) were associated with increased risk of gestational diabetes mellitus occurrence (p<0.05). According to Receiver Operating Characteristic (ROC) curve for significant variables and determination of sensitivity and specificity of cut points, the area under the curve was greater for hematocrit than other variables.  Conclusion: Elevated hematocrit level among all red blood cell indices in second trimester had the strongest association with increased risk of GDM occurrence. This important issue requires special attention to hematocrit levels when administrating iron supplements in pregnancy.